Insights into the role of legionella effectors on host metabolic perturbations - Wang, Zhihao; Song, Lei (Frontiers in Cellular and Infection Microbiology, 2024)
Legionella infection, the causative agent of Legionnaires’ disease, represents a significant threat to human health. The pathogenesis of this infection is intricately linked to the complex interactions between the bacterium and its host, resulting in profound metabolic perturbations. Central to these metabolic shifts is the bacterium’s modulation of lipid metabolism, with changes in lipid synthesis and breakdown modifying membrane composition and function. These alterations can influence cellular signaling and immune responses, further contributing to disease progression. It also disrupts glucose utilization and lipid metabolism, altering cellular energy production and immune responses. Additionally, Legionella infection perturbs amino acid and protein metabolism, affecting protein synthesis and degradation, leading to changes in cellular functions and immune responses. This mini-review underscores the complexity of metabolic perturbations in Legionella infection and their significance in host-pathogen interactions. Understanding these metabolic shifts provides valuable insights into the pathogenesis of Legionnaires’ disease and could lead to the development of novel therapeutic strategies.